2009 8th IEEE International Symposium on Mixed and Augmented Reality 2009
DOI: 10.1109/ismar.2009.5336485
|View full text |Cite
|
Sign up to set email alerts
|

Real-time in-situ visual feedback of task performance in mixed environments for learning joint psychomotor-cognitive tasks

Abstract: This paper proposes an approach to mixed environment training of manual tasks requiring concurrent use of psychomotor and cognitive skills. To train concurrent use of both skill sets, the learner is provided real-time generated, in-situ presented visual feedback of her performance.This feedback provides reinforcement and correction of psychomotor skills concurrently with guidance in developing cognitive models of the task.The general approach is presented: 1) Sensors placed in the physical environment detect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…The study indicates that it is important to determine relevant key features of the task (as also was suggested by Huegel, Celik, Israr, & O'Malley, 2009;Todorov et al, 1997) and to provide feedback only about these key features, in order to not overwhelm the learner with irrelevant information. In realistic virtual reality systems, abstract augmented concurrent feedback has been reported to be detrimental to manual dexterity training of dental students (Wierinck, Puttemans, Swinnen, & van Steenberghe, 2005) but has been rated to be beneficial by medical educators and students for learning clinical breast exams (Kotranza, Lind, Pugh, & Lok, 2009) and has been shown to be effective for robotic laparoscopy training (Judkins, Oleynikov, & Stergiou, 2006).…”
Section: Abstract Visualizationsmentioning
confidence: 99%
“…The study indicates that it is important to determine relevant key features of the task (as also was suggested by Huegel, Celik, Israr, & O'Malley, 2009;Todorov et al, 1997) and to provide feedback only about these key features, in order to not overwhelm the learner with irrelevant information. In realistic virtual reality systems, abstract augmented concurrent feedback has been reported to be detrimental to manual dexterity training of dental students (Wierinck, Puttemans, Swinnen, & van Steenberghe, 2005) but has been rated to be beneficial by medical educators and students for learning clinical breast exams (Kotranza, Lind, Pugh, & Lok, 2009) and has been shown to be effective for robotic laparoscopy training (Judkins, Oleynikov, & Stergiou, 2006).…”
Section: Abstract Visualizationsmentioning
confidence: 99%
“…In addition, real-time interaction permits visualizing results instantly, so students are able to take decisions based on these results to reach their learning goals, increasing their learning performance and cognitive skills (Kotranza, Lind, Pugh, & Lok, 2009). But it is also possible to interact collaboratively, so virtual environments also boost interaction and collaboration among students.…”
Section: Advantages Of Using Virtual Technologies In Educationmentioning
confidence: 99%
“…25 In this way, AR technology can provide synthetic objects for teaching, such as anatomical parts or rare items for science laboratories. Kotranza et al (2009) 26 showed an AR system in clinical medicine that embedded touch sensors in a physical environment, collected sensor data to measure learners' performances and then transformed the performance data into visual feedback.…”
Section: Discussionmentioning
confidence: 99%